Studies on the Ice Flow in the Bare Ice Area near the Allan Hills in Victoria Land, Antarctica - Nishio, Fumihiko; Annexstad, John O. (1980)
P(論文) The mechanism of accumulation of a large number of meteorites in the bare ice area near the Allan Hills in South Victoria Land has been investigated by surveying a triangulation chain of 20 stations, 15km in total length, during the 1978-79 and 1979-80 field seasons. The horizontal and vertical components of surface velocities of the ice sheet in the bare ice area at 18 stations and the parameters of surface strains at 18 triangles of the chain were obtained. The horizontal velocity of the ice sheet at the station farthest from the datum point is 2.51m/year and the velocity vector principally points in a northeast direction which is perpendicular to the contour lines. The magnitude of horizontal velocities gradually decreases from a maximum at station 20 to nearly zero at the stations near the Allan Hills. The vertical movements of the bare ice are emergent at a rate of 4.5cm/year on the average in the region of high meteorite accumulation, while in the area of the further inland the vertical ice flow shows small submergence velocities. Ablation rates are ranging from 4.2 to 7.0cm/year with an average of 5.7cm/year and are balanced on the average by the emergent velocity of the ice in the meteorite accumulation area. Compressive strains are predominant in most of the triangle areas and the horizontal dilatation of each triangle area is negative (horizontal convergence). These characters of ice flow are favorable for accumulation of a large number of meteorites on the bare ice surface in a small area, and also support a proposed hypothesis by NAGATA (1978) on the mechanism of concentration of Yamato meteorites within the Meteorite Ice Field near the Yamato Mountains in East Queen Maud Land, where the triangulation survey has also shown an upward flow of ice. departmental bulletin paper